Development of highly efficient and scalable free-standing electrodes for the fabrication of hydrazine-O2 fuel cell. (31st May 2019) - Zhao, Aijuan; Sun, Haijie; Chen, Lingxia; Huang, Yufang; Lu, Xingjie
Abstract: The electrochemical oxidation of hydrazine at the electrode surface offers great scientific and technological interests because of the more favorable energy and power densities compared to the PEMFCs. In the present work, we report an easy and scalable electrochemical deposition method for the preparation of highly efficient, noble metal-free hydrazine oxidation electrocatalysts for the fabrication of hydrazine-O2 fuel cell (HOFCs). For the electrode preparation, we have employed readily available environmental friendly metals (Co and Ni) which have shown better catalytic activity than the state-of-the-art catalysts in terms of onset potential (−0.22 V versus Hg/HgO) and current density. The employed, catalyst synthesis strategy has the capability to prepare the electrodes without employing any catalysts binder, using highly conductive nickel mesh support as a current collector.